Medieval art, architecture and archaeology in the dioceses of Aberdeen and Moray
1 online resource
Keywords: "The British Archaeological Association Conference of 2014, based at Aberdeen University, surveyed the medieval heritage of Aberdeenshire and Moray. The opening historical papers establish the political, economic and administrative context of the region, looking at both the secular and religious worlds and including an examination of Elgin Cathedral and the bishops' palaces. The discoveries at the excavations of the kirk of St. Nicholas, which have revealed the early origins of religious life in Aberdeen city, are summarised here prior to full publication"--Amazon.com.